2013
DOI: 10.4209/aaqr.2012.11.0314
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Particulate Matter Concentrations in Makkah, Applying a Statistical Modeling Approach

Abstract: Particulate matter originates from a variety of sources in Makkah, Saudi Arabia. Since Makkah is situated in an arid region and is a very busy city due to its religious importance in the Muslim world, PM 10 concentrations here exceed the international and national air quality standards set for the protection of human health. The main aim of this paper is to model PM 10 concentrations with the aid of meteorological variables (wind speed, wind direction, temperature, and relative humidity) and traffic related ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 22 publications
2
52
2
Order By: Relevance
“…The SWS can influence visibility, aerosol distribution, and air quality (Munir et al 2013;Onat and Stakeeva 2013;Zhu and Liang 2013;Wu et al 2013;Zhang et al 2016a), and decreases in the SWS can intensify the accumulation of aerosols, thereby reducing the solar radiation received at the surface. Lin et al (2015) found that surface dimming was associated with decreases in SWS in some regions with severe air pollution in China.…”
Section: Introductionmentioning
confidence: 99%
“…The SWS can influence visibility, aerosol distribution, and air quality (Munir et al 2013;Onat and Stakeeva 2013;Zhu and Liang 2013;Wu et al 2013;Zhang et al 2016a), and decreases in the SWS can intensify the accumulation of aerosols, thereby reducing the solar radiation received at the surface. Lin et al (2015) found that surface dimming was associated with decreases in SWS in some regions with severe air pollution in China.…”
Section: Introductionmentioning
confidence: 99%
“…Shaltout et al (2013) focused on the chemical composition of PM 2.5 during June-August 2011 at an industrial site and a residential site in Taif, which is a mountain city about 140 km east of Jeddah city. Rushdi et al (2013) presented PM 2.5 and PM 10 concentrations at ten locations within the capital city Riyadh during June andNovember 2006 andFebruary andMay 2007. The longest data series on air quality parameters (NO x , NO, NO 2 , SO 2 , CO, O 3 and PM 10 ) was published by the Hajj Research Institute, Umm Al-Qura University in Makkah (Munir et al, 2013b), which is about 70 km to the east of Jeddah. This study presented the temporal variations over 12 valid years during 1997-2012.…”
Section: Introductionmentioning
confidence: 99%
“…Higher concentration in summer is probably caused by high wind speed and high temperature a common phenomenon in Saudi Arabia which increases atmospheric turbulence leading to a greater amount of resuspension of dust from roadside and blowing sand particles from the surrounding areas. It is worth mentioning that resuspension of dust particles and windblown sand and dust particles along with road traffic and other combustion processes are the main sources of particulate matter in Saudi Arabia [18], [19]. However the model does not differentiate in PM 10 originated from different sources.…”
Section: B Airq223 Model Inputsmentioning
confidence: 99%